2017
DOI: 10.1097/pai.0000000000000445
|View full text |Cite
|
Sign up to set email alerts
|

Primary Carcinoid Tumor of the Renal Pelvis Arising From Intestinal Metaplasia: An Unusual Histogenetic Pathway?

Abstract: This report portrays a unique presentation of carcinoid tumor arising from intestinal metaplasia of the pelvic urothelium, and supports its histogenesis from urothelial intestinal metaplasia and neuroendocrine hyperplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…The renal parenchyma was the apparent source of carcinoids in 76.2% of patients with non-horseshoe kidneys. In two cases, the predominant site was the renal pelvis (4.3%) (Kuba et al 2017, Rudrick et al 1995. The isthmus or paraisthmus area was predominantly implicated in cases with horseshoe kidneys.…”
Section: Discussionmentioning
confidence: 97%
“…The renal parenchyma was the apparent source of carcinoids in 76.2% of patients with non-horseshoe kidneys. In two cases, the predominant site was the renal pelvis (4.3%) (Kuba et al 2017, Rudrick et al 1995. The isthmus or paraisthmus area was predominantly implicated in cases with horseshoe kidneys.…”
Section: Discussionmentioning
confidence: 97%
“…The current research found intestinal metaplasia as a sequelae of chronic infection of renal pelvis, which may be an etiological factor in the occurrence of neuroendocrine cell hyperplasia and carcinoid tumor in the renal pelvicaliceal system. 10 , 42–46 …”
Section: Discussionmentioning
confidence: 99%
“…These tumors could be derived from pancreatic tissue, neural crest, multipotent stem cells, urothelial metaplasia, or metastases from an unknown primary. [ 27 28 ] They tend to occur in association with congenital and acquired renal abnormalities, patients do not usually develop carcinoid syndrome, and around 30% of tumors are incidentally diagnosed. [ 29 ] They are solitary, unilateral, and slow-growing masses larger than 4 cm and advanced at diagnosis.…”
Section: Discussionmentioning
confidence: 99%